Development of a low-cost portable system to measure emissions from flexfuel vehicles - Forcetto, André Luiz Silva (2022)
Large urban centers such as the Metropolitan Area of Sao Paulo are subject to the pollution of soil, water, and air, where vehicles are an important source of atmospheric pollutants. In Brazil, the automotive fleet is mainly composed of flexfuel cars, fueled with ethanol as well as gasoline in any proportion. The control of the emissions and measurement of Emission Factors (EF) from vehicles is done by diverse methods, for example, in-tunnel experiments, remote sensing, standardized laboratory tests, and by the real driving emissions (RDE) test, running the vehicle in the roads coupled to a Portable Emissions Measurement System (PEMS). Furthermore, the RDE test was included in the new phases of the PROCONVE (Brazilian Program to Control Air Pollution from Automotive Vehicles) for homologation proposals. However, commercial PEMS are costly, heavy, and hard to be customized, while low-cost sensor technology is becoming even more available and, reliable. Thus, this research had the goal of developing a compact and low-cost PEMS, able to be applied in flexfuel vehicles. The low-cost PEMS was evaluated in vehicular emissions laboratory, reaching coefficients of determination R2 above 0.94 for CO2 and CO and 0.73 for THC. The data from real-world tests performed with the low-cost PEMS were condensed in EF, indicating relevant tendencies for improving mathematic models for pollutant emissions from vehicles. The results, in comparison to the values from standardized laboratory tests, point to an increase above 50% in the emissions at low urban speeds, at high accelerations and vehicle-specific power (VSP) demand, and close to 10 times increment for cold start emission. The most representative EF parameters were the vehicle speed and the VSP, with R2 close to 0.90 for tendency curves expressed by first- and second-degree equations. The final result was a light, small dimensions, liable system, expending only a fraction of the value of a commercial device, and these characteristics could ease future academic research on vehicle emissions, including motorcycles.